2003
DOI: 10.1038/nmat1035
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-mechanism map for nanocrystalline metals by molecular-dynamics simulation

Abstract: Molecular-dynamics simulations have recently been used to elucidate the transition with decreasing grain size from a dislocation-based to a grain-boundary-based deformation mechanism in nanocrystalline f.c.c. metals. This transition in the deformation mechanism results in a maximum yield strength at a grain size (the 'strongest size') that depends strongly on the stacking-fault energy, the elastic properties of the metal, and the magnitude of the applied stress. Here, by exploring the role of the stacking-faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
410
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 770 publications
(448 citation statements)
references
References 30 publications
17
410
2
1
Order By: Relevance
“…However, defined as metals with structural features less than 100 nm, they are not nanocrystalline because their grain sizes are usually larger than 100 nm. Molecular dynamics (MD) simulations have shown that in NC metals dislocations may be emitted from and disappear at grain boundaries without accumulation [9][10][11], providing support to the widely accepted belief that they have intrinsically diminutive strain hardening.…”
mentioning
confidence: 86%
“…However, defined as metals with structural features less than 100 nm, they are not nanocrystalline because their grain sizes are usually larger than 100 nm. Molecular dynamics (MD) simulations have shown that in NC metals dislocations may be emitted from and disappear at grain boundaries without accumulation [9][10][11], providing support to the widely accepted belief that they have intrinsically diminutive strain hardening.…”
mentioning
confidence: 86%
“…Hence, there have been a number of studies in face-centered cubic (fcc) metals investigating the grain size associated with this behavior, the role of grain boundaries and stacking fault energy in nucleating dislocations and the subsequent behavior of dislocations afterward. [145][146][147][148] What is generally observed with the grain boundary dislocation activity is that the dislocation density increases, which results in both dynamic recovery and increased dislocation annihilation; this ultimately limits the capacity for dislocation storage. 4 This low saturation of dislocation density leads to the very low strain-hardening rate typically seen.…”
Section: Strain Hardeningmentioning
confidence: 99%
“…13 Deformation twins usually form in NC fcc metals via mechanisms different from those proposed for coarsegrained materials. 2 Several twinning mechanisms have been proposed for and observed in NC fcc metals, including the coincidental overlapping of wide stacking fault ribbons, 14,15 partial emissions from grain boundaries, 2,5,6,11,[14][15][16][17][18] grain boundary splitting and migration, 15,16 random activation of partials ͑RAP͒, 2 dislocation cross-slip mechanism, 19 selfpartial multiplication mechanisms, [20][21][22] and dislocation rebound mechanism. 22 Single twins with two coherent boundaries are observed most frequently under high-resolution electron microscopy ͑HREM͒ and by molecular dynamics simulations.…”
mentioning
confidence: 99%